Commentary: Giuseppe Campani (1635‐1715, Rome, Italy): the First Use of a Microscope in Medicine and Surgery. Issue 2 (February 2018) - Brogna, Christian; Millesi, Matthias; Fiengo, Leslie; Richardson, Mark; Bhangoo, Ranjeev; Ashkan, Keyoumars; Türe, Uğur
Abstract : Abstract : Giuseppe Campani (1635‐1715) was a polymath in Rome, Italy, during the Scientific Revolution in the XVIIth century. In particular, he forged the screw barrel microscope and was manufacturing his own lenses for microscopes and telescopes. He mastered the art of lens grinding. Those lenses have been analyzed with modern methods and turned out to be of extremely good quality, shining light on the fact that Giuseppe Campani mastered the theories of optics. Moreover, in a letter that Giuseppe Campani sent to Pope Innocent XI, he clearly described the use of a microscope for the examination of wounds of legs. This letter dates back to 15 August 1686 and is the first evidence of the use of microscopes to analyze wounds, sores, and anatomic specimens in medical and surgical settings. MG Yasargil previously showed the lithography accompanying this letter and was the first to recognize its great importance. We accessed this original letter in the Vatican Library, and for the first time we have translated it from Latin to English in order to unveil its significance in the context of the Scientific Revolution and the history of medicine and surgery.